Analisis Efektivitas Produk Rahn Tasjily Tanah Dalam Kemudahan Permodalan dan Peningkatan Perekonomian Nasabah pada PT Pegadaian Syariah Cabang Setia Budi Medan - Atika Pratiwi; Tuti Anggraini; Nusantri Yanti (MES Management Journal, 2023)
This study aims to determine the level of effectiveness of Rahn Tasjily's soil products in facilitating capital at PT. Pegadaian Syariah Setia Budi Medan Branch and to determine the level of effectiveness of Rahn Tasjily's land products in improving the economy of customers at PT. Pawnshop Syariah Setia Budi Medan Branch. This study uses qualitative methods with primary and secondary data sources and data collection methods using observation, interviews, and documentation, while data analysis uses descriptive analysis methods. Based on the results of the study, it can be concluded that the land yields of Rahn Tasjily found at the Pawnshop Syariah Setia Budi Medan are in accordance with the indicators of the effectiveness of the ease of capital, as evidenced by explanations from staff and customers who use Rahn Tasjily's produce. Rahn Tasjily's land yield is also in accordance with the indicators of the effectiveness of improving the economy as evidenced by the explanations of several customers whose economy has improved after using this product. Although in the manufacture of this product there are still several obstacles such as a long and difficult process and full caution in choosing prospective customers who will use this product and a great risk if the customer fails to pay, this product is still quite popular among the public so that this product is considered effective, because in its implementation Rahn Tasjily's financing of this land has met the effectiveness aspects, and indicators of the effectiveness of the ease of capital and economic improvement. In the perspective of Islamic economics, this financing is also in accordance with the principles of Islamic economics, such as there is no element of usury, the transactions carried out are permissible transactions and not prohibited activities. Keywords: Effectiveness, Rahn Tasjily Tanah, Sharia Pawnshop.